Simulation of dark lanes in post-flare supra-arcades - II. A contribution to the remote sensing of the coronal magnetic field - Schulz, Walkiria (2010)
We integrate the MHD ideal equations to simulate dark void sunwardly moving structures in post-flare supra-arcades. In Costa et al. we could numerically reproduce the observations described in Verwichte et al. We showed that the dark tracks are plasma vacuums generated by the bouncing and interfering of shocks and expansion waves, upstream an initial slow magnetoacoustic shock produced by a localized deposition of energy modelled as a pressure perturbation. The same pressure perturbation produces a transverse to the field or perpendicular magnetic shock giving rise to non-linear waves that compose the kink-like plasma void structures, with the same functional sunward decreasing phase speed and period's constancy with height, as those determined by the observations. In this Letter we accomplish a study of sensitivity to initial and background physical conditions of the phenomenon. With the aim of contributing to the remote sensing of the corona we describe the characteristics of different void structures in terms of physical conditions, i.e. magnetic field intensity and pressure perturbation, given a background density. © 2010 The Authors. Journal compilation © 2010 RAS.